SANKSI PIDANA BAGI ANAK YANG BERHADAPAN DENGAN HUKUM PERSPEKTIF FIQIH JINAYAH - Rafid, Noercholis; Saidah, Saidah (LPPM IAIN Parepare, 2018)
This paper aims to determine the criminal acts of children along with criminal sanctions given as preventive measures. By using qualitative data and through juridical and theological normative approaches it was found the conclusion is criminal acts of children are acts carried out contrary to the Law contained in the Criminal Code. The cause of child delinquency is caused by internal factors, namely family and external, namely environmental conditions. In jurisprudence jurisprudence there is no criminal sanction against the child for the crime he committed, because he is considered not yet competent legally, but a judge is allowed to sanction educational actions so that the child can be better. Criminal violations committed by a child who is faced with the law should be charged to his parents or handed over to the state to be sanctioned in the form of guidance. This is because minors have not yet been forgiven.